1999
DOI: 10.2115/fiber.55.7_306
|View full text |Cite
|
Sign up to set email alerts
|

Large Deformation of Woven Fabrics under Free Shearing Uni-axial Load.

Abstract: : Free shearing deformation of woven fabrics under uniaxial tensile load was analyzed, Equations to calculate the strains along the yarn directions and crossing angle of yarns from the cloth strains were derived.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…However, the composition of viscoelastic constants in solution of the equation is unknown. For the sixelement model which connected models of equation (1) and equation (2) in parallel, we set the strain and total force of the six-element model as ε and F, and express first and second-order differentiations of strains and forces with respect to t by dot such as  and   , and ̇ and ̈. From the relations of the force and strain, we obtain following relations; …”
Section: Analytical Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the composition of viscoelastic constants in solution of the equation is unknown. For the sixelement model which connected models of equation (1) and equation (2) in parallel, we set the strain and total force of the six-element model as ε and F, and express first and second-order differentiations of strains and forces with respect to t by dot such as  and   , and ̇ and ̈. From the relations of the force and strain, we obtain following relations; …”
Section: Analytical Approachmentioning
confidence: 99%
“…Crossing yarns in the bias direction of fabric are more easily deformed than those in the yarn direction. [1][2][3] Bias-cut fabric is able to give a soft look and drape, and is thus usually used for flared skirts or dresses. Bias-cut fabric is also partly used for circular skirts.…”
mentioning
confidence: 99%
“…Buckenham 9 compared the KES-F and bias extension test methods and concluded that the bias extension test is more appropriate for characterizing fabrics in the trellising deformation. Takatera et al 10 carried out the bias extension test using the rod-clamp method and concluded that deformation in a fabric sample tested with the bias extension method cannot correspond to the pure shear state when large loads are applied. Potluri et al 11 proposed a wide strip bias extension test and investigated the meso-scale shear deformation of textile composites.…”
mentioning
confidence: 99%
“…done by many other researchers [9][10][11][12][13][14][15][16][17], and a great number of testers have been developed. Although those works opened a new era of understanding the mechanical properties of woven fabrics and designing the fabric tensile testers, it should be noted that because of the complex mechanical properties of woven fabrics, the existing testers which are theoretically capable of making the measurement are still unsuitable to be applied into the practical use or have serious limitations.…”
mentioning
confidence: 99%